2023
DOI: 10.1186/s12870-023-04227-6
|View full text |Cite
|
Sign up to set email alerts
|

Selenium uptake, translocation, subcellular distribution and speciation in winter wheat in response to phosphorus application combined with three types of selenium fertilizer

Abstract: Background Selenium (Se) deficiency causes a series of health disorders in humans, and Se concentrations in the edible parts of crops can be improved by altering exogenous Se species. However, the uptake, transport, subcellular distribution and metabolism of selenite, selenate and SeMet (selenomethionine) under the influence of phosphorus (P) has not been well characterized. Results The results showed that increasing the P application rate enhanced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 104 publications
1
1
0
Order By: Relevance
“…Previous reports consistently revealed that the uptake efficiency of SeMet was much higher than that of selenate, selenite and SeOMet [19][20][21]. Our latest result revealed that SeMet uptake was markedly inhibited by the aquaporin inhibitor (AgNO 3 ), indicating that rice absorbs SeMet primarily via aquaporin.…”
Section: Introductionsupporting
confidence: 57%
“…Previous reports consistently revealed that the uptake efficiency of SeMet was much higher than that of selenate, selenite and SeOMet [19][20][21]. Our latest result revealed that SeMet uptake was markedly inhibited by the aquaporin inhibitor (AgNO 3 ), indicating that rice absorbs SeMet primarily via aquaporin.…”
Section: Introductionsupporting
confidence: 57%
“…Recently, Wu et al [ 151 ] conducted high-throughput transcriptomic sequencing in Aegilops tauschii , providing valuable insights into Se metabolism in this species for future research. Similar other recent studies can be conducted in wheat to gain a deeper understanding of the molecular and physiological mechanisms involved in Se metabolism [ 136 , 151 , 152 ].…”
Section: Main Textmentioning
confidence: 75%